Financial Performance and Shares of PT Bukit Uluwatu Villa TBK Before, During and After The Covid-19 Pancemic - Budi Artha, I Wayan; Santika, Putu; Nugraha, Surya (Akademi Komunitas MAPINDO, 2024)
Financial Performance of PT Bukit Uluwatu Villa Tbk was not healthy before the Covid-19 Pandemic, its performance got worse with the Covid-19 Pandemic and its performance only improved after new investors entered by putting in additional capital in the second year after the Covid-19 Pandemic ended. It is estimated that as tourism returns to normal, its financial performance will improve and its financial ratios will become healthier. Unhealthy financial performance results in a decline in the company's share price, and as a result the company's market capitalization value also declines. Improving financial performance by improving the capital structure and increasing sales as well as making efficiencies in the company's operational aspects. Improving financial performance will certainly boost the increase in share prices which have been slumping. Promotion/marketing strategies to increase sales should still pay attention to sustainability (sustainable green tourism marketing) in order to reduce (minimise) the negative effects of tourism on people's lives. Keywords: Covid-19 Pandemic, Tourism, Financial Performance, Share Performance, Financial Ratios